Kajian Balok – Kolom Utama Dan Sambungannya Pada Rumah Panggung Sistem Floor Lifting Method - Sukoyo Sukoyo (Politeknik Negeri Semarang, 2015)
Semarang is one of the cities that most of its territory is always inundated by tidal water, especially in areas near to the beach. Most of the houses in these areas often take in rob water, so the house becomes less healthy and less comfortable. Therefore we want to make a home stage floor can be raised with the increase in tidal water using a jacking system, which we call the stage house floor lifting method. The success of the house lifting depends on the model of the main beams and columns and its connection.Therefore we try to overcome the problem by doing research with the aims: (a) Planning main column model (b). Planning main beam model (c). Planning the main beam - column connection system. Methode research done by making several alternative column model, beam and joint and then tested in the laboratory, which is then compared with the real burden for small home (<30m2). Outcomes of this research are (a). The column used is made of reinforced concrete with a hole interval of 20 cm. (b). The beam used are profile IWF 15. (c). Connection beam and column using 4 bolts 12 mm.